New records of Cheilotheca (Ericaceae, Monotropoideae ) from China including the description of a new species - Wu, Lei; Jiang, Ri-Hong; Yang, Jin-Cai; Liu, Yan (Phytotaxa, 2016)
The first record of Cheilotheca from China is reported here with the description of a new species, C. crocea, from evergreen broadleaved forest in south-central Guangxi of southern China. The new species is morphologically most similar to C. malayana, but it can be easily distinguished from the latter by its equal length filaments and elongate anthers with 2-longitudinal slits at dehiscence (vs. unequal length filaments and short anthers with a single terminal slit). The detailed morphological characters together with illustrations, diagnostic comparisons and habitat are presented.